The European Union Trust Fund for Africa: what implications for future EU development policy? - Clare Castillejo (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The European Union Emergency Trust Fund for Africa (EUTF) is a central part of the EU's engagement on migration. It has generated both high aspirations and serious concerns regarding its aims, activities, and relation¬ship to broader trends in migration and development policy. The EUTF's stated goal is to “address the root causes of destabilisation, forced displacement and irregular migration”, an aim that is widely seen as unrealistic. However, key actors have other ambitions for the fund. These include demonstrating action on migration in response to political pressure, incentivising African cooperation on migration management, and using the fund's flexibility to develop innovative programming. It is arguably through such innovation that the EUTF could add most value. The EUTF is perceived by many African partners as part of a European-imposed migration agenda that prioritises EU interests over African ones. While experiences vary between countries and projects, African ownership within the EUTF is undoubtedly weaker than within traditional European cooperation instruments. The EUTF risks alienating African partners and overlooking local priorities, knowledge and capacities. The selection of EUTF projects and partners has been criticised as ad hoc and untransparent. Member states' implementing agencies play the largest role in implementation, and some clearly see the fund as a source of finance for their regular programming. This raises concerns over whether EUTF projects add value to existing programming and are the best fit for either the trust fund's goals or local context. The most controversial aspect of the EUTF is its potential to divert development aid in service of the EU's migration agenda, including in ways that contradict EU development and human rights commitments. This appears to be part of a broader trend towards the securitisation of EU development assistance. The EUTF also undermines EU development commitments by skewing aid allocations towards countries based on their migration profile, and by abandoning aid effectiveness principles such as alignment. There are several measures that could improve the EUTF and make the most of the opportunities that it offers. These include: more transparent and consultative project development; stronger engagement with local actors and needs; greater emphasis on seeking out “best fit” implementers; and drawing on existing lessons, evidence and approaches. However, if the EUTF is ultimately an indication of the future direction of EU development cooperation, this does not bode well for the EU's prioritisation of development principles, its long-term interests, or its relationship with Africa. Several processes lie ahead that will influence the future of EU-Africa relations. These must be used to examine how Europe and Africa can work together more constructively to address migration in ways that meet both their interests.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik